Keterampilan Berpikir Tingkat Tinggi (HOTS) Mahasiswa dalam Mengeksplorasi Kearifan Lokal Jambi Melalui Pembelajaran Berbasis Proyek - Fitri Astriawati; Winda Dwi Kartika; Bambang Hariyadi (Biosfer: Jurnal Pendidikan Biologi, 2026)
In the era of 21st-century education, higher education institutions are expected not only to transmit knowledge but also to cultivate students’ Higher-Order Thinking Skills (HOTS). One promising approach to achieving this goal is integrating local wisdom into the learning process through the Project-Based Learning (PjBL) model. This study aimed to explore Jambi’s local wisdom through PjBL and analyze its impact on students' HOTS achievement. The research employed a quasi-experimental design with a non-equivalent pre-test and post-test experimental group design. The sample consisted of 27 Biology Education students at the University of Jambi, selected through purposive sampling. HOTS were measured using multiple-choice tests for analyzing and evaluating skills, and a holistic assessment rubric for the creating skill. Students’ HOTS scores were analyzed using a paired-sample t-test, while the effect size was calculated using Cohen’s d. The results showed that the exploration of Jambi’s local wisdom through project-based learning had a large effect on improving students’ HOTS, as indicated by the t-test results [t(20) = 23.972; p < 0.001; d = 5.2]. The greatest improvement occurred in the creating indicator (49.22%), followed by evaluating (31.48%) and analyzing (20.14%). These findings indicate that integrating Jambi’s local wisdom into the PjBL model is effective in developing students’ HOTS and supports contextual learning aligned with the principles of Education for Sustainable Development (ESD). Therefore, project-based learning that incorporates local wisdom can serve as a transformational strategy in curriculum development that meets the demands of 21st-century skills.